Academics' perception of systems engineering and applied research projects. Issue 1 (6th September 2021) - Honoré‐Livermore, Evelyn; Fossum, Knut Robert; Veitch, Erik
Abstract: There is an increased complexity in applied research projects that demand more researcher skills, especially in managing the research project and interdisciplinary work. Researchers receive little training in how to manage such projects, yet most manage to deliver project results. There is a tradition of project management and systems engineering which benefits complex development projects in industrial settings. Despite the apparent benefits, we found limited application of either project management or systems engineering practices in academia. Furthermore, we found barriers to applying these practices in the first place, such as a lack of clear guidance or tools for their execution. A case study based on 18 semi‐structured interviews provides a perspective on academic research projects, and how the application of project management and systems engineering in an academic setting shows promise to improve the realization of concept design.